Answer:
Explanation:
Using the point slope equation of a line to solve the question
y-y0=m(x-x0) where (x0,y0) is the point and m is the slope of the unknown line perpendicular to the given line.
Rewriting the equation given in the form y = MX+c
2x+5y+8 = 0
5y = -8-2x
y = -8/5-2x/5
From the equation, m = -2/5
Since the unknown line is perpendicular to the give line, the slope of the given line will be;
M = -1/(-2/5)
M = 5/2
Substituting the point and the slope into the equation above
y-(-6) = 5/2(x-(-3))
y+6 = 5/2(x+3)
y+6 = 5x/2+15/2
2y+12 = 5x+15
2y-5x = 15-12
2y-5x = 3 gives the required equation of the line